Design and Implementation of a Low-Cost Real-Time Control Platform for Power Electronics Applications - Travieso-Torres, J; Travieso-Torres, J; Rojas-Lobos, F; Diaz-Diaz, M; Uriarte-Gonzalez, M; Aravena-Carrasco, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In recent years, different off-the-shelf solutions for the rapid control prototyping of power electronics converters have been commercialised. The main benefits of those systems are based on a fast and easy-to-use environment due to high-level programming. However, most of those systems are very expensive and are closed software and hardware solutions. In this context, this paper presents the design and implementation of a control platform targeting at the segment in between expensive off-the-shelf control platforms and low-cost controllers. The control platform is based on the Launchpad TMS320F28379D from Texas Instruments, and it is equipped with an expansion board that provide analogue-to-digital measurements, switching signals and hardware protections. The performance of the control platform is experimentally tested on a 20 kVA power converter. © 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).